PEMBELAJARAN SENI BUDAYA DAN PRAKARYA DALAM UPAYA MEMBANGUN KARAKTER PESERTA DIDIK DI MADRASAH IBTIDAIYAH - Deva Meia Maharani; Istiyati Mahmudah (Titik Fokus Karya, 2025)
This study explores the role of cultural arts education in character development among elementary school students, specifically in the context of MIN 3 Kota Palangka Raya. The primary aim of this research is to examine how arts education fosters not only artistic skills but also essential character values such as empathy, tolerance, creativity, independence, and social responsibility. Through qualitative research, involving in-depth interviews with teachers, this study highlights the ways in which cultural arts education can contribute to the formation of positive student character. The findings suggest that the integration of character education within arts education enables students to better appreciate diversity, engage in cooperative work, and express themselves creatively. Additionally, arts education provides a safe space for students to overcome self-doubt and fear of failure, increasing their confidence and sense of achievement. By focusing on both the cognitive and emotional aspects of learning, cultural arts education proves to be a powerful tool in shaping well-rounded individuals. Furthermore, it encourages the development of critical thinking, problem-solving skills, and an understanding of local cultural heritage. This research underscores the importance of integrating character education within arts curricula, as it not only enhances students' artistic competencies but also supports their social and emotional development. Ultimately, the study concludes that cultural arts education plays a pivotal role in nurturing students into responsible, empathetic, and creative individuals, prepared to contribute positively to society.